1959
DOI: 10.1136/bmj.1.5115.148
|View full text |Cite
|
Sign up to set email alerts
|

Menstruation and Acute Psychiatric Illnesses

Abstract: This investigation was undertaken to determine whether acute psychiatric admissions to hospital were in any way influenced by the premenstruum or by menstruation. For many years it has been believed that psychiatric illness was apt to exacerbate at the time of the menstrual period, and in this paper an attempt is made to determine if such a relationship exists. It has been prompted by the recognition of the premenstrual syndrome and its successful treatment (Greene and Dalton, 1953).As there are many ways in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

1967
1967
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(52 citation statements)
references
References 3 publications
3
47
0
2
Order By: Relevance
“…From this we concluded that oestrogen also has a weak neuroleptic-like effect on schizophrenic symptoms. An analogous variation in symptom severity over the menstrual cycle was also reported by Hallonquist et al (1993), and similar clinical observations had previously been published by Dalton (1959) and Endo et al (1978). Seeman and Cohen (1999), early proponents of the oestrogen hypothesis, tested the hypothesis that an earlier onset of functional oestrogen secretion with puberty might be associated with a later onset of schizophrenia in women.…”
Section: Testing the Oestrogen Hypothesis At Different Levels (Domain 5)supporting
confidence: 87%
“…From this we concluded that oestrogen also has a weak neuroleptic-like effect on schizophrenic symptoms. An analogous variation in symptom severity over the menstrual cycle was also reported by Hallonquist et al (1993), and similar clinical observations had previously been published by Dalton (1959) and Endo et al (1978). Seeman and Cohen (1999), early proponents of the oestrogen hypothesis, tested the hypothesis that an earlier onset of functional oestrogen secretion with puberty might be associated with a later onset of schizophrenia in women.…”
Section: Testing the Oestrogen Hypothesis At Different Levels (Domain 5)supporting
confidence: 87%
“…In addition, there are scattered reports of periodic psychoses associated with certain phases of the human menstrual cycle [e.g. 21,26,50], and female psy chiatric patients tend to be admitted to hospital more frequently during these phases of the cycle [1,19,38], both of which phenomena may reflect disturbed dopa mine function. Fluctuations in the efficacy of neurolep tics over the cycle have been reported [48], and women appear to be more prone than men to develop parkinson ism, akathisia and tardive dyskinesias in response to neuroleptic drugs [23],…”
Section: Discussionmentioning
confidence: 99%
“…The oestrogen level is known to have two peaks, one occurring in the premenstrual period and the other at ovulation (Dalton, 1959;Kopell, Lunde, Clayton & Moos, 1969). There are other hormonal changes which also have been observed to have two peaks in the menstrual cycle (Greene & Dalton, 1953;Dalton, 1959;Janowsky, Gorney & Mandell, 1967;Margerison, Anderson & Dawson, 1964;Bruce & Russell, 1962;Sargent & Weinman, 1966;Southam & Gonzaga, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…There are other hormonal changes which also have been observed to have two peaks in the menstrual cycle (Greene & Dalton, 1953;Dalton, 1959;Janowsky, Gorney & Mandell, 1967;Margerison, Anderson & Dawson, 1964;Bruce & Russell, 1962;Sargent & Weinman, 1966;Southam & Gonzaga, 1965). Although it has not been possible to relate the changes definitely to any one hormone, it is still possible to see how a hormonal change could affect the pitch estimates because of their known general effect on the body.…”
Section: Discussionmentioning
confidence: 99%